2016
DOI: 10.1007/s12192-015-0654-4
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside protects against bleomycin-induced pulmonary fibrosis: activation of Nrf2-antioxidant signaling, and inhibition of NF-κB and TGF-β1/Smad-2/-3 pathways

Abstract: Pulmonary fibrosis (PF) can severely disrupt lung function, leading to fatal consequences. Salidroside is a principal active ingredient of Rhodiola rosea and has recently been reported to protect against lung injures. The present study was aimed at exploring its therapeutic effects on PF. Lung fibrotic injuries were induced in SD rats by a single intratracheal instillation of 5 mg/kg bleomycin (BLM). Then, these rats were administrated with 50, 100, or 200 mg/kg salidroside for 28 days. BLM-triggered structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 40 publications
2
48
1
1
Order By: Relevance
“…It is of interest that salidroside has been demonstrated to have protective effects against pulmonary fibrosis. Tang et al demonstrate that in bleomycin-induced pulmonary fibrosis salidroside can inhibit IκBα phosphorylation and nuclear factor kappa B (NF-κB) via activating Nrf2-antioxidant signaling [25]. The recombinant TGF-β1-induced EMT-like changes can be reversed and the expression of TGF-β1 and the phosphorylation of its downstream targets, Smad-2/-3, were weakened by salidroside.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that salidroside has been demonstrated to have protective effects against pulmonary fibrosis. Tang et al demonstrate that in bleomycin-induced pulmonary fibrosis salidroside can inhibit IκBα phosphorylation and nuclear factor kappa B (NF-κB) via activating Nrf2-antioxidant signaling [25]. The recombinant TGF-β1-induced EMT-like changes can be reversed and the expression of TGF-β1 and the phosphorylation of its downstream targets, Smad-2/-3, were weakened by salidroside.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rhodiola rosea extracts and salidroside was able to increase the expression of antioxidant enzymes (e.g. GPx) and activate the nuclear erythroid 2-related factor 2 (Nrf2) pathways in rats to protect against bleomycin-induced pulmonary fibrosis in rats [68] and to reverse ultraviolet B induced DNA damages in HaCaT cells [69], respectively.…”
Section: The Anti-stress Properties Of Rhodiola Rosea Lmentioning
confidence: 99%
“…It was seen that salidroside could protect against epirubicin-induced early left ventricular regional systolic dysfunction in patients with breast cancer . Surprisingly, salidroside has also been reported to protect against PF in a recent work (Tang et al, 2016). It was reported that salidroside attenuated BLM-triggered structure distortion, collagen overproduction, excessive inflammatory infiltration, and pro-inflammatory cytokine release, and oxidative stress damages in lung tissues (Tang et al, 2016).…”
Section: Glycosidesmentioning
confidence: 99%
“…-SD rats (BLM, 7.5 U/kg) Tang et al (2016) Astragalin Diospyros kaki L.f. -Wistar rats (BLM, 2.5 mg/kg), ICR mice (LPS, 5 mg/kg) - Akgedik et al (2012) and Zhang et al (2015) Curcumin Curcuma longa L. PMVEC, primary FB (IR, 2 Gy) C57BL/6 mice (0.5 μg LPS or 13.5 Gy IR), CBA/J mice (reovirus 1/L, 10 7 PFU) FB (TGF-β, 6 ng/ml), PF patients Lee et al (2010), Smith et al (2010), Avasarala et al (2013) and Jiang and Zhang (2015a) EGCG Camellia sinensis (L.) Kuntze FB WI−38 (TGF-β1, 10 ng/ml) Wistar rats (BLM, 6.5 U/kg), SD rats (IR, 22 Gy) - Sriram et al (2009aSriram et al ( , 2009bSriram et al ( , 2015 and You et al (2014) Corilagin Caesalpinia coriaria (Jacq. )…”
Section: Scutellaria Baicalensismentioning
confidence: 99%